IMPLEMENTASI MANAJEMEN WAKTU DALAM PENGELOLAAN PENDIDIKAN UNTUK MENCAPAI TUJUAN PENYELENGGARA PENDIDIKAN ISLAM YANG PROFESIONAL - Muhammad Fauzi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Islamic education requires effective time management to achieve the goals of professional educational administration. This research aims to investigate the implementation of time management within the context of Islamic education to enhance professionalism in educational administration. The research methodology combines literature review with qualitative analysis. This study highlights the importance of effective time scheduling in curriculum planning, teaching, and extracurricular activities within Islamic educational institutions. The proper implementation of time management enables educators to optimize the use of time in teaching, cater to students' needs, and facilitate their spiritual and intellectual growth. Research findings indicate that good time management significantly contributes to the professionalism of educators and the quality of Islamic education. Effective time management helps create a structured learning environment, motivates students, and enhances teaching efficiency. The research findings emphasize that good time management plays a crucial role in developing educator professionalism and in achieving sustainable goals in Islamic education. Effective time management allows educators to build a structured learning environment, support comprehensive student growth, and improve teaching efficiency. This research provides a profound insight into how the implementation of effective time management can be a key aspect in achieving high-quality and professional Islamic educational objectives.